2018
DOI: 10.1111/bcpt.13140
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of antidepressants in suicides findings from the Friuli Venezia Giulia Region, Italy, 2005‐2014

Abstract: Although continued use of antidepressants (AD) has been found to be associated with a lower risk of suicide, AD discontinuation is reported repeatedly. The aim of this case‐control study, thus, was to assess whether discontinuation to AD was associated with an increased risk of suicide, according to different genders and age groups. The Social and Health Information System of Friuli Venezia Giulia Region, Italy, was used to collect data on suicides, diagnoses and AD use from 2005 to 2014. We selected, as cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…The highest risk of using ADs after COVID-19 infection was found in unvaccinated subjects aged 65 years and older, both females and males, independently of being hosted in a residential facility. In contrast, vaccinated subjects were less likely to use ADs in all age groups, and the association was even not signi cant in all male age groups ADs in FVG were prescribed to a higher extent to females and to the elderly, in line with other research from the region [34,35,19]. A previous study also indicated a higher use of ADs during the pandemic compared to the predicted, concluding that this might be due to a rise of depressive and anxiety symptoms, but information on the incidence of AD use at the individual level was not provided [19].…”
Section: Discussionsupporting
confidence: 84%
“…The highest risk of using ADs after COVID-19 infection was found in unvaccinated subjects aged 65 years and older, both females and males, independently of being hosted in a residential facility. In contrast, vaccinated subjects were less likely to use ADs in all age groups, and the association was even not signi cant in all male age groups ADs in FVG were prescribed to a higher extent to females and to the elderly, in line with other research from the region [34,35,19]. A previous study also indicated a higher use of ADs during the pandemic compared to the predicted, concluding that this might be due to a rise of depressive and anxiety symptoms, but information on the incidence of AD use at the individual level was not provided [19].…”
Section: Discussionsupporting
confidence: 84%
“…This may be due to a higher incidence of sleeping disturbances during the Italian lockdown, for which these drugs are broadly used (Castelpietra et al, 2017). In contrast, TCAs showed no increase, possibly due to both their common use for pain disorders (Trifiro et al, 2013), and that GPs are less likely to prescribe TCAs for psychiatric conditions, because of their lower safety compared to newer ADs (Castelpietra et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, only AD prescriptions issued by GPs, psychiatrists, and other public physicians were available from the register, albeit this represents 90% of the prescriptions (Castelpietra et al, 2015). Thirdly, we were not able to assess the adherence to ADs, a common limitation of studies based on prescription registers (Castelpietra et al, 2019;Castelpietra et al, 2017;Rabeea et al, 2021). Fourthly, we could not adjust the analyses for other factors, such as socioeconomic status or psychiatric diagnoses.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long-term use of BDZ is very common [8], particularly in the elderly [10,18,4,5], whether this was so prominent in NHs might be related to different factors. In FVG, most of prescriptions at the primary care level, including NHs, are filled by GPs [27], and GPs had been previously observed to dispense BDZ for long time to older patients [19]. On the other hand, BDZs are usually prescribed to inpatients by specialized doctors, who are less prone to dispensing these drugs [28].…”
Section: The Use Of Benzodiazepinesmentioning
confidence: 99%